The Routledge companion of performance-related concepts in non-European languages - Fischer-Lichte, Erika; Schenka, Astrid; Jost, Torsten 1981- (Routledge advances in theatre & performance studies, 2024)
"Investigating more than 70 key concepts relating to the performing arts in more than six non-European languages, this volume provides a groundbreaking research tool and one-of-a-kind reference source for theatre, performance and dance studies worldwide. The Companion features in-depth explorations of and expert introductions to a select number of performance-related key concepts in Arabic, Chinese, Japanese, Korean, Yorùbá as well as the Indian languages Sanskrit, Hindi and Tamil. Key concepts—such as Furǧa فرجة in Arabic, for example, or Jiadingxing 假定性 in Chinese, Gei 芸 in Japanese, Ìparadà in Yorùbá and Imyeon 이면 in Korean—that defy easy translation from one language to another (and especially into English as the world’s lingua franca) and that reflect culturally specific ways of thinking and talking about the performing arts are thoroughly examined in in-depth articles. Written by more than 60 distinguished scholars from around the globe, the articles describe in detail each concept’s dynamic history, its flexible scope of meaning and current range of usage. The Companion also includes extensive introductions to each language section, in which internationally renowned experts explain how the presented key concepts are situated within, and are constitutive of, distinct and dynamic epistemic systems that have different yet always interlinked histories and orientations. Offers a fascinating insight into the unique histories, characteristics, and orientations of linguistically and culturally distinct epistemic systems related to the performative arts Contains extensive cross-references and bibliographies An invaluable research tool and one-of-a-kind reference source for scholars and students worldwide and across the humanities, especially in the fields of theatre, performance, dance, translation, area and cultural studies An accessible handbook for everybody interested in performance cultures and performance-related knowledge systems existing in the world today. This volume provides an invaluable research tool and one-of-a-kind reference source for scholars and students worldwide and across the humanities, especially in the fields of theatre, performance, dance, translation and area studies, history (of science and the humanities) and cultural studies."--Book cover